(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
PhilipArthur Larkin ( 9 August 1922 – 2 December 1985 ) is widely regarded as one ofthe greatest English poets of the latter half of the twentieth century. Hisfirst book of poetry , The North Ship , was published in 1945 , followed by twonovels , Jill (1946) and A Girl in Winter (1947) , but he came to prominence in1955 with the publication of his second collection of poems , The Less Deceived, followed by The Whitsun Weddings (1964) and High Windows (1974). Hecontributed to The Daily Telegraph as its jazz critic from 1961 to 1971 ,articles gathered together in All What Jazz : A Record Diary 1961-71 (1985),and he edited the Oxford Book of Twentieth Century English Verse (1973). He wasoffered , but declined , the position of poet laureate in 1984 , following thedeath of John Betjeman.